Optimization of low sintering temperature for colossal permittivity and humidity resistance in TiO2 based ceramics - Yasumin Mingmuang; Narong Chanlek; Masaki Takesada; Ekaphan Swatsitang; Prasit Thongbai (Scientific Reports)
Abstract This study investigates the colossal permittivity (CP) and humidity resistance of (Sn1/2Nb1/2)0.025Ti0.975O2 ceramics. Increasing the sintering temperature enhanced both density and grain growth, with the fine–grained structure proving essential for achieving a high dielectric constant (ε′ ~ 2.2 × 104) and maintaining low dissipation factors (tanδ ~ 0.011) at a reduced sintering temperature of 1150 °C. At an elevated sintering temperature of 1210 °C, optimal dielectric properties were observed, yielding ε′ ~ 1.0 × 104 and an ultra–low tanδ of ~ 0.004, attributed to highly resistive grain boundaries. The CP response is linked to semiconducting grains, supported by the presence of Ti3+ resulting from Ti4+ substitution by Nb5+. The minimal variation in ε′ with temperature suggests suitability for capacitor applications, with ε′ exhibiting little dependence on DC bias (0–30 V/mm). Optimized sintering conditions yielded stable CP properties with minimal sensitivity to humidity (30%–90% RH) over a range of temperatures (25–85 °C) and frequencies (102–106 Hz). These findings underscore the potential of (Sn1/2Nb1/2)0.025Ti0.975O2 ceramics for advanced capacitors in varied environmental and operational conditions.